2014
DOI: 10.1007/s00248-014-0497-z
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Community Composition and Fermentation Patterns in the Rumen of Sika Deer (Cervus nippon) Fed Three Different Diets

Abstract: Sika deer (Cervus nippon) rely on microorganisms living in the rumen to convert plant materials into chemical compounds, such as volatile fatty acids (VFAs), but how the rumen bacterial community is affected by different forages and adapt to altered diets remains poorly understood. The present study used 454-pyrosequencing of bacterial 16S ribosomal RNA (rRNA) genes to examine the relationship between rumen bacterial diversity and metabolic phenotypes using three sika deer in a 3 × 3 latin square design. Three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 68 publications
6
40
1
Order By: Relevance
“…Van Gylswyk (1995) reported that Succiniclasticum ruminis plays a major role in converting succinate to propionate as the sole energy-yielding mechanism. Certain bacterial members within the family Succinivibrionaceae produce succinate as the principal fermentation product, and a number of exogenous sources of hydrogen could stimulate the formation of succinate (Pope et al 2011;Stackebrandt and Hespell 2006), which was dominant in the rumen of sika deer (Li et al 2015). Bacteria within the family Lachnospiraceae produced butyrate (Cotta and Forster 2006), which was also dominant in the rumens of moose and various arctic ruminants (Ishaq and Wright 2012;Ishaq and Wright 2014) as well as in the foregut of dromedary camels in Australia (Samsudin et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Van Gylswyk (1995) reported that Succiniclasticum ruminis plays a major role in converting succinate to propionate as the sole energy-yielding mechanism. Certain bacterial members within the family Succinivibrionaceae produce succinate as the principal fermentation product, and a number of exogenous sources of hydrogen could stimulate the formation of succinate (Pope et al 2011;Stackebrandt and Hespell 2006), which was dominant in the rumen of sika deer (Li et al 2015). Bacteria within the family Lachnospiraceae produced butyrate (Cotta and Forster 2006), which was also dominant in the rumens of moose and various arctic ruminants (Ishaq and Wright 2012;Ishaq and Wright 2014) as well as in the foregut of dromedary camels in Australia (Samsudin et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The amount of ammonia was measured according to the phenol-sodium hypochlorite method as previously described (Li et al 2015). The concentrations of VFAs in the rumen were analyzed via gas D r a f t chromatography (TP-2060F, Beijing BeifenTianpu Instrument Technology Co. Ltd., Beijing, China) with a flame ionization detector and a PEG-20M H 3 PO 4 glass column.…”
Section: Measurement Of Ruminal Fermentation Parametersmentioning
confidence: 99%
“…The high degree of stabilization of bacterial flora, both G+ and G−, in the rumen of deer whose diet was supplemented with the pellets may have improved the digestive activity of enzymes produced by these microorganisms, which indirectly contributed to the improvement observed in the condition of the deer (2,7,23).…”
Section: Resultsmentioning
confidence: 99%
“…Herbivore microbial symbionts, often residing in the guts of animals, have been implicated in aiding plant biomass breakdown (Hess et al , 2011; Kudo, 2009; Talbot, 1977; Adams et al , 2011), plant defense compound remediation (Wang et al , 2010; Adams et al , 2013; Boone et al , 2013), and nutrient supplementation (Warnecke et al , 2007; Hansen and Moran, 2011; LeBlanc et al , 2013). Microbial communities differ between hosts that specialize on different substrates (Muegge et al , 2011) and changes in these communities and their functional capacity are integral to their hosts’ transition to utilizing novel substrates (Hammer and Bowers, 2015; Delsuc et al , 2013; Li et al , 2015; Kohl et al , 2014; 2016). This phenomenon is not isolated to herbivores – in many systems, gut microbial communities are influence by the inputs of their hosts (Goffredi et al , 2005; Roman et al , 2015; Muegge et al , 2011; Youngblut et al , 2019; Wang et al , 2011; Li et al , 2016).…”
Section: Introductionmentioning
confidence: 99%